Role of Omeprazole in Enhancement of Antibiotic Resistance in E. coli - Al-Bakri, S. A.; Jabri, R. R.; Ajeel, E. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
E. coli was isolated, and it was Gram-negative rod bacteria that was colony circular, regular edged, thick somewhat glitter and  viscous(less). It was lactose fermenter bacteria and belongs the family of Enterobacteriaceae. E. coli showed sensitivity to all used antibiotics except Erythromycin (E), Cloxacellin (CX), Rifampin (RA), Cephalothin (KF), Ampicillin (AM), and Penicillin (P). The experimental results of antibiotic sensitivity of E. coli in media containing different concentrations of omeprazole, a proton pump inhibitor, showed an enhancement of resistance by decreasing the sensitivity of E. coli inversely with drug concentration against the antibiotics that E. coli was sensitive to. It seems that omeprazole changed cell membrane potential of E. coli which led to depolarization of cell membrane as a result of inhibition of the proton pump mechanism. This made the bacterial cell not willing to uptake antibiotics